Quick fabrication of aeronautical complicated structural parts based on stereolithography - Jiangping Zhou; Zhongliang Lu; Kai Miao; Zhe Ji; Yin Dong; Dichen Li (Propulsion and Power Research, 2015)
Investment casting based on stereolithography (SL) has the characteristics of short production cycle and low cost, which is especially suitable for fabricating complex aeronautical parts without metal dies. But there are some problems during the fabrication process, such as low surface accuracy caused by the staircases of resin prototype, shell cracking caused by higher thermal stress during the sintering process and so on. Taking an engine turbine stator as a fabrication example, the surface accuracy of resin prototype under the effect of coating method was investigated using the laser confocal microscopy; what’s more, both theoretical analysis and finite element analysis (FEA) were combined and compared to reveal the thermal stress field of ceramic shell during pyrolyzing and sintering process under different situation. It was founded that the surface staircases of the resin prototype was eliminated and the surface quality was improved after coating process, the thermal stress was decreased and shell cracking was avoided by sintering the ceramic shell with the inner hollow resin prototype under the heating rate of 5 °C/min. The result showed that, the metal turbine stator had high dimensional accuracy of CT4-CT6 and had a good surface finish within Ra 3.2.